Acoustic microscope study of the elastic properties of fluorapatite and hydroxyapatite, tooth enamel and bone. - Gardner, T; Elliott, J; Sklar, Z; Briggs, G (1992)
Measurements of Rayleigh velocity and attenuation were taken in single mineral crystals of hydroxyapatite and fluorapatite at angular intervals relative to their c axes, using an acoustic microscope. These results are compared with the values that were calculated using the elastic constants of apatite from Yoon and Newnham [(1969) Am. Miner. 54, 1193-1197.] and Katz and Ukraincik [(1971) J. Biomechanics 4, 221-227.]. The slowness curves of various wave modes are plotted and discussed in relation to cross-coupling effects that were found to cause instability in measurements of attenuation for the c axes direction. Velocity measurements were taken in specimens of tooth enamel and bone. Here comparisons are made with the values that were calculated by modelling the 'z' scan response of the microscope, using published data for the elastic and acoustic properties. Comparisons are also made with the measurements on single crystals, since apatite is a major component of enamel and bone.